N′-[1-(4-Nitrophenyl)ethylidene]acetohydrazide - Yu-Feng Li; Lian-Cai Du; Fang-Fang Jian (Acta Crystallographica Section E, 2009)
The title compound, C10H11N3O3, was prepared by the reaction of acetohydrazide and 1-(4-nitrophenyl)ethanone. The asymmetric unit contains two crystallographically independent molecules. Inversion-related molecules form dimers, in which two N—H...O hydrogen bonds generate an intermolecular R22(8) ring.